2004
DOI: 10.1210/jc.2003-032021
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Manipulation of Benign Metastasizing Leiomyomas: Report of Two Cases and Review of the Literature

Abstract: Benign metastasizing leiomyomas (BMLs) occur predominantly in women during reproductive years. The condition is characterized by uterine leiomyomas associated with the development, typically years later, of slow-growing metastatic lesions. The most commonly affected organs are the lungs, but BMLs have been reported in lymph nodes, deep soft tissues, mesentery, bones, the central nervous system, and the heart. In many cases, these lesions have an indolent course and are discovered rather incidentally. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 50 publications
(23 reference statements)
2
131
1
2
Order By: Relevance
“…Finally, because of their uterine origin and the presence of high levels of ERs and PRs, medical treatment with drugs such as tamoxifen or raloxifene, both selective ER modulators, may be effective in cases where surgical resection is incomplete or not clinically indicated. 18,20,25 In summary, our study supports the notion that 'benign metastasizing leiomyoma' is a result of monoclonal, hematogenous spread of a benignappearing uterine leiomyoma. This tumor possesses many morphologic, immunohistochemical, and molecular features characteristic of a benign neoplasm despite its potential for metastastic spread, which if neglected, may lead to shortened survival.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, because of their uterine origin and the presence of high levels of ERs and PRs, medical treatment with drugs such as tamoxifen or raloxifene, both selective ER modulators, may be effective in cases where surgical resection is incomplete or not clinically indicated. 18,20,25 In summary, our study supports the notion that 'benign metastasizing leiomyoma' is a result of monoclonal, hematogenous spread of a benignappearing uterine leiomyoma. This tumor possesses many morphologic, immunohistochemical, and molecular features characteristic of a benign neoplasm despite its potential for metastastic spread, which if neglected, may lead to shortened survival.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the non-implanted myoma fragments disclosed decreased expressions of both ERα and PR compared with implanted lesions, and this result suggested the disseminated fragments with strong positive ERα and PR might be essential in the development of PM implantations. Our study also demonstrated that depletion of oestrogen decreased the angiogenesis, proliferation and implantations, and the result was correlated with previous studies which demonstrated shrinkage of benign metastatic leiomyomatosis after bilateral salpingo-oophorectomy (BSO) surgery [53][54][55][56]. The duration of sex steroid hormone exposure after laparoscopic morcellation might also be a risk factor for the development of PMs [26].…”
Section: Discussionsupporting
confidence: 90%
“…However, there have been described very infrequent situations in which the tumor presents a distant progression of smooth muscle cell to other organs. There are different types of growing pattern including Benign Metastasizing Leiomyoma (BML), intravascular leiomyomatosis and disseminated peritoneal leiomyomatosis [1]. The most afflicted organs are the lungs [2], but there have been documented extrapulmonary involvement in heart, spine, bone, skull base, omentum and mesentery, lymph nodes and deep soft tissue.…”
Section: Discussionmentioning
confidence: 99%